2015
DOI: 10.1021/ac504193z
|View full text |Cite
|
Sign up to set email alerts
|

Browning Phenomenon of Medieval Stained Glass Windows

Abstract: In this work, three pieces of historical on-site glass windows dated from the 13th to 16th century and one archeological sample (8th century) showing Mn-rich brown spots at their surface or subsurface have been characterized by optical microscopy and Scanning Electron Microscopy coupled with Energy Dispersive X-ray spectroscopy. The oxidation state of Mn as well as the Mn environment in the alteration phase have been characterized by X-ray absorption spectroscopy at the Mn K-edge. Results show that the oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
(99 reference statements)
1
13
0
Order By: Relevance
“…The XAFS technique has also been used to study ancient and medieval glasses [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. Different studies focused on the determination of the origin of color in ancient and medieval glasses because this kind of information is important to understand the manufacturing technique of ancient glassware and potteries [ 154 , 155 , 158 , 159 , 160 , 165 ]. Recently, Farges and Cotte published a chapter in a book where they update as compared to the most recent review papers published on the application of XAFS technique to study cultural heritage [ 166 ].…”
Section: Examples Of Using the Xafs Technique To Study The Atomic mentioning
confidence: 99%
See 2 more Smart Citations
“…The XAFS technique has also been used to study ancient and medieval glasses [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ]. Different studies focused on the determination of the origin of color in ancient and medieval glasses because this kind of information is important to understand the manufacturing technique of ancient glassware and potteries [ 154 , 155 , 158 , 159 , 160 , 165 ]. Recently, Farges and Cotte published a chapter in a book where they update as compared to the most recent review papers published on the application of XAFS technique to study cultural heritage [ 166 ].…”
Section: Examples Of Using the Xafs Technique To Study The Atomic mentioning
confidence: 99%
“…Among different studies where XAFS was used to study medieval glasses, we can cite, for example the work by Ferrand et al [ 160 ] that analyzed by XAFS three pieces of historical on-site glass windows dated from the 13th to 16th century and one archeological sample from the 8th century that showed Mn-rich brown spots at their surface or subsurface [ 160 ]. Based on XAFS results, they observed that the oxidation state of Mn is different compared to fresh glass confirming that a modification of the Mn environment occurred.…”
Section: Examples Of Using the Xafs Technique To Study The Atomic mentioning
confidence: 99%
See 1 more Smart Citation
“…The spotty brown coloration of the original incarnate glass is caused by precipitation of four‐valent manganese ions present as secondary pyrolusite . However, as observed by Ferrand et al on historical (13th‐16th century) window glass, extended brown coloration contains mainly Mn 3+ ions. Sometimes precipitation of the spinel hausmannite was observed…”
Section: Extension To Nuclear Waste Glassesmentioning
confidence: 92%
“…To minimize photoreduction effects commonly reported for Mn-bearing phases (Bargar et al, 2005;Manceau et al, 2012;Ferrand, 2014;Ferrand et al, 2015), the beam size used was 50 × 50 µm 2 , and the photon flux was reduced together with data collection time. XANES spectra were collected from 6505 to 6630 eV with a 0.2 eV step size, and 0.4 s counting time per step.…”
Section: µ-X-ray Absorption Near Edge Structure (Xanes) Spectroscopymentioning
confidence: 99%